Two-versus three-screw osteosynthesis of the mandibular condylar head: A finite element analysis. (March 2022) - Schönegg, Daphne; Müller, Günter T.; Blumer, Michael; Essig, Harald; Wagner, Maximilian E.H.
Abstract: Titanium screws are commonly used for osteosynthesis of mandibular condylar head fractures. Evidence suggests that the insertion of three screws may result in better fracture stability. Two screws only, on the other hand, could reduce adverse effects, mainly bone resorption. This study aimed to investigate the biomechanical differences in mandibular condylar head osteosynthesis with two versus three titanium screws using finite element analysis. A finite element model of the mandible with a right type P condylar head fracture fixed with two or three titanium screws was analyzed in ANSYS Mechanical. The geometry of the model assembly was constructed in ANSYS Spaceclaim. Biomechanical load boundary conditions were obtained from a validated musculoskeletal model in AnyBody Modeling System™. The preprocessing of the finite element model and mapping of the obtained boundary conditions was done in docq VIT. Fracture displacement, fragment deformation, von Mises stress distribution, and reaction forces within the screws were evaluated in ANSYS for three different loading scenarios. Finite element analysis showed similar results when comparing osteosynthesis with two versus three titanium screws for all three loading scenarios. Contralateral molar loading resulted in the highest stress on both the fracture and the screws with the maximum von Mises stress being found at the condylar neck. Stress concentration within the screws was found in the fracture gap and was higher in the lateral fragment. In all scenarios, maximum von Mises stress values were smaller when forces were distributed among three screws. However, stability was also adequate when two screws were used. Mandibular condylar head osteosynthesis with two titanium screws appears to provide sufficient fracture stability. Further clinical studies are needed to clarify the implications of these results. Graphical abstract: Image 1 Highlights: Novel qualitative finite element model of type P mandibular condylar head fracture. Analysis with validated boundary conditions for accurate modeling. Three loading scenarios depict clinically realistic postoperative conditions. Two-screw osteosynthesis seems to provide adequate fracture stability. Minimally invasive two-screw treatment is therefore a reasonable treatment option.